O tema avaliação escolar na escolarização de crianças com deficiência intelectual - Silva, Rosangela Miranda De Souza E [UNIFESP] (2020)
The theme school evaluation in the schooling of children with intellectual disabilit ie s has been approached in academic production and this production must be analyzed, because in addition to its scientific purposes, it bases references chosen for teacher trai ning. We did a research based on the reading of articles academically endorsed a s specific and, for this reason, we surveyed the production on the topic within the scope of the Revista Brasileira de Educação, Revista Educação Especial, Revista Diálogo e Pe rspectivas em Educação Especial and in the Working Group 15 (WG 15 special educa ti on) from ANPED, under a time frame from 1988 (Federal Constitution) to 2018. We intend to identify who are the researchers and groups that have built these references and we produced an inventory specifying with which concepts / words this universe has b ee n delimited. The results pointed to the prevalence of assessment based on clinical diagnosis to the detriment of pedagogical assessment, demonstrating how intentionality in e valuative action is based on the biomedical model of disability, labeling the st ud ent as a potential failure in relation to his schooling.